Princípios globais de contabilidade gerencial: relação de práticas gerenciais com a reputação corporativa e com o desempenho das companhias abertas brasileiras - Costa, Ingrid Laís de Sena (2017)
Economic changes related to models of organizational structure, people's behavior and values, and new business models require a new positioning of managerial accounting, since this is one of the leading providers of information for the decision-making process of the organizations. Thus, it is increasingly required that managerial accounting provide a better basis to support such decisions. In this sense, the Global Management Accounting Principles (GMAP) have emerged as good management practices that companies can implement. Based on these discussions, the objective of this research is to analysis the relationship of GMAP with the corporate reputation and the performance of the Brazilian public companies. The sample analyzed comprised 342 companies listed in B3 during the period from 2010 to 2016. In order to respond to the research problem, the methodology consisted in the construction of an index of adequacy to the recommendations proposed by the GMAP, observing the impacts of the good practices of the managerial accounting upon the organizational performance and the corporate reputation of the companies. Data analysis was performed using statistical estimates such as the use of mean and Principal Component Analysis for the estimation of the index, and regressions for the observation of the proposed relations. The results obtained showed that, through the managerial accounting index, companies attend more than 50% of the practices that should be observed by the organizations according to the GMAP, that is, companies prefer not to disclose in their reports the managerial information about their management. It was also observed that after 2014 there was an increase in the index relative to managerial practices, which provides indications of a greater concern of the companies towards the adopted practices. With respect to the corporate reputation of the companies, a positive relationship with the management practices was observed, evidencing that the reputation of the company must be a strategic decision of the organization, planned to reach the established objectives. As for the performance of the companies, it was noticed that the management practices adopted by them affect more their market performance and the expectations of future growth, thus demonstrating a positive relation, as it is assumed by the CGMA proposal and institutional theory once management practices are routines incorporated into the organizational identity of companies, reflecting better long-term results.